EVOLUTION OF APPROACHES TO FORMATION OF THE CONCEPT OF SUSTAINABLE DEVELOPMENT OF THE ENTERPRISE (INNOVATIVE ECONOMY, 2024)
Komandrovska V.Ye. EVOLUTION OF APPROACHES TO FORMATION OF THE CONCEPT OF SUSTAINABLE DEVELOPMENT OF THE ENTERPRISEPurpose. The aim of the article is to study the emergence and evolution of the term “sustainable enterprise development”, existing approaches to interpreting its essence in economic literature, and shaping the definition from the author's understanding.Methodology of research. The method of scientific abstraction, analysis and synthesis was used when studying the evolution of the concepts of sustainable enterprise development – in determining the theoretical and methodological approaches to the essence of the concept of "sustainable enterprise development"; system and integrated approaches – in identifying factors that determine the features of the definition of the term "sustainable enterprise development" for the Economy 5.0.Findings. The article examines the evolution of approaches to the formation of the concept of sustainable enterprise development under the influence of global challenges and technological progress, increasing demands for responsible and environmentally friendly business conduct. The evolution of the approaches of leading scientists to the interpretation of the concept under study and the substantiation of the author's vision from the standpoint of the Economy 5.0 concept is systematized.Originality. The definition of the concept of "sustainable enterprise development" is proposed, taking into account the features of the Fourth Industrial Revolution and the transition to the Economy 5.0. It is determined that the sustainable development of an enterprise is a strategic approach to enterprise management that combines innovative technologies and a high level of automation with a responsible society aimed at achieving economic prosperity, social ethics and a balance between economic, environmental, social and cultural aspects, in order to create a viable and resilient business model.Practical value. The practical value is determined by the possibility of using the results of conducted research by enterprises to form a strategy for sustainable development, taking into account current trends.Key words: sustainable development, sustainable development concept, Economy 5.0, innovation.
Keywords: sustainable development; sustainable development concept; Economy 5.0; innovation.